(3GdfGaY jhe GdMTQs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s ((3Ydj Hf CMeO Hf eMeO GdHMQGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj Od Ydi hLhH hLhOg GaJbGQ GdeecfGJ (B... (3bGd (B... (3GdHGH GdMOj YTQ ajeG jLH Ydi YGeI Gdecdajf ef eYQaI CUhd GdOjf , Cbhd(B: (3EfeG cGf gPG GdHGH GdMGOj YTQ dCf GdeUfas
(3BNQgG (B:s
(3BNQgG(B: (3GdQGHY ef GdBeQ hGdfGgj ef GdVQO GdMGUd HSHH GdCeQ hGdfgj eG (B... (3Ch Edi CMO ef GdeSdejf aEf ZdH YfOgeG MUhd Pdc GQJaY GdhLhH CjkVG hjLHGf HGdbdH hGddSGf hGdHOQ dG jfJbd Edi GdCUYH eY GfLGY GdCSgds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 282s
(3GdPQjYI, L (B24: 13s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds